2021
DOI: 10.1088/1361-6641/ac0578
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption study of defects in reactively sputtered GaN films displaying large variation of conductivity

Abstract: Undoped GaN films were epitaxially grown on c-sapphire by rf magnetron reactive sputtering of GaAs at different N 2 percentages in Ar-N 2 sputtering atmosphere. These films display a large increase in conductivity from ∼10 −6 Ω −1 cm −1 to ∼10 2 Ω −1 cm −1 with decrease of N 2 in sputtering atmosphere from 100% to 10%. X-ray photoelectron spectroscopy reveals a monotonous decrease of N/Ga ratio, concurrently with increase of uncoordinated/interstitial Ga in the films, with decrease of N 2 percentage in sputter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 73 publications
4
5
0
Order By: Relevance
“…The EDX data also confirm the absence of arsenic and the presence of oxygen impurity (~3 at.%) in all the films. These results are in agreement with earlier XPS and SIMS studies of undoped GaN films [18,44], which also indicated the possibility of excess nitrogen in the films grown at higher N2 percentages, as in the case of Si-doped films. All the films reveal the presence of ~2 at.% Si, irrespective of N2 percentage in sputtering atmosphere.…”
Section: Resultssupporting
confidence: 92%
“…The EDX data also confirm the absence of arsenic and the presence of oxygen impurity (~3 at.%) in all the films. These results are in agreement with earlier XPS and SIMS studies of undoped GaN films [18,44], which also indicated the possibility of excess nitrogen in the films grown at higher N2 percentages, as in the case of Si-doped films. All the films reveal the presence of ~2 at.% Si, irrespective of N2 percentage in sputtering atmosphere.…”
Section: Resultssupporting
confidence: 92%
“…In the case of Si-doped GaN films, EDX measurements have shown the presence of ∼2 at.% Si in all the films along with oxygen impurity (∼3 at.%) and confirmed the absence of arsenic [42]. It was also found that the N/Ga ratio in Si-doped films decreased with decrease of N 2 percentage in sputtering atmosphere, similar to the observations made for undoped GaN films [42,44].…”
Section: Resultssupporting
confidence: 80%
“…It has earlier been shown [20,42] that both undoped and Si-doped GaN films grown at 100% N 2 possess large hydrostatic strain due to the presence of N interstitials (known to be acceptors in GaN [45,46]), which decreased drastically with decrease of N 2 percentage in sputtering atmosphere. The high resistivity of undoped GaN films grown at 100% N 2 and its decrease with N 2 percentage was hence primarily attributed to the strong compensation by N interstitials and their subsequent decrease [44]. Thus, the low carrier concentration of Sidoped GaN films grown at 100% N 2 is also attributed to the compensation by N interstitials and its subsequent increase in the film grown at 75% N 2 to the substantial decrease of N interstitials, as shown earlier [42].…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations